Case Report: Concurrent retinal vasculitis and optic neuritis in systemic lupus erythematosus - Jin, Di; Liu, Xun; Wang, Yuwei; Fang, Longjiang; Nie, Weiduo; Li, Chen; Li, Sheng-Guang; Li, Ming (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disease that can affect the ocular system, with retinal vasculitis and optic neuritis being rare but serious manifestations. We present a case of a 26-year-old female with newly diagnosed SLE who developed both retinal vasculitis and optic neuritis, leading to progressive visual impairment. She was successfully treated with methylprednisolone and rituximab, achieving significant visual recovery. A review of existing literature highlights the diagnostic challenges, pathophysiology, and optimal treatment strategies for such cases. Our findings emphasize the importance of early recognition and aggressive immunosuppressive therapy in improving patient outcomes.